OPTIMIZATION OF STAPLE PRODUCTS USING THE SUPPLY CHAIN OPERATION REFERENCE (SCOR) TO CUSTOMER SATISFACTION IN CENTRAL JAVA - Muhammad Shobur; Syahreen Nurmutia; Gilang Ardi Pratama (SINERGI, 2021)
The role of the Supply Chain affects the value of domestic products that arise in an area is not the same as the income received by residents of the area. It can be seen that the staple products sector dominates 61.55% of the distribution of products in Central Java. So, this is an important factor in measuring the Supply Operations Chain that occurs in these commodities. The high costs incurred in this sector encourage us to continue to improve our operational performance to reduce costs as low as possible. The condition is what the public/consumers want so that the gap between production costs and distribution costs of existing products is not too far away. This study aims to measure consumer satisfaction with the Supply Chain in the area and optimize the Supply Chain model that can be done to improve operational processes in the upstream (supplier) and downstream (distribution channels) of the Supply Chain in Central Java. The data analysis method used is the Supply Chain Operation Reference (SCOR). This model serves to weigh the importance of measuring customer satisfaction with the Supply Chain in the area, and efforts to improve operational performance can be made by minimizing failure in the process so that delivery to consumers is on time. The results of the SCOR model show that Asset, Agility, and Cost are variables that must be improved in the logistics process in Central Java.